ENT 600 : AHSB Bersekutu Sdn Bhd / Ezreen Ayu Khatijah Azman ... [et al.] - Azman, Ezreen Ayu Khatijah; Basori, Noor Izyana; Abdul Razak, Rushila; Zainol Ariffin, Siti Saudah; Wan Mohamed, Wan Ismahani (2018)
This case study is about AHSB Bersekutu Sdn Bhd, an electrical company which offers wiring services, located at Batu Caves, Selangor. In order to know deeper regarding this company, an interview session with the founder had been done recently. The interview questions are mainly about company background and SWOT analysis. From the SWOT analysis, our team learns to interpret the strengths, weaknesses, opportunities, and threats which can help in developing a proper business strategy. The SWOT analysis is one of the best tools that have been widely used by other successful companies for a better planning. Other than that, we are able to learn how to develop alternative solutions to handle the problems faced by the company.